Transformational Leadership and the TLIM Model for Strengthening Organizational Capacity and Competitive Advantage in Madrasah - Yuli Nur Rohmawati; Abdul Malik Karim Amrullah; Slamet (Mudir: Jurnal Manajemen Pendidikan, 2026)
Islamic junior secondary schools (madrasah) in Indonesia face persistent challenges of quality disparity and intensifying institutional competition, demanding effective leadership strategies to sustain organizational performance and public trust. This study aimed to analyze the transformational leadership strategies employed by the principal of MTsN 3 Malang in realizing organizational capacity and competitive advantage. Employing a qualitative case study design, data were collected through in-depth interviews, participatory observation, and document analysis involving the principal, vice-principals, teachers, and educational staff as key informants; data validity was ensured through source and method triangulation, followed by condensation, display, and conclusion-drawing as analytical procedures. The findings revealed that transformational leadership was operationalized through three integrated strategies: (1) participatory and data-driven strategic decision-making directed at strengthening flagship programs and educational service quality; (2) mobilization and empowerment of human resources through collaborative culture-building, collective commitment, and professional support for teachers and staff; and (3) institutional change and innovation encompassing excellence program development, student achievement coaching, and cultivation of a competitive academic culture. These three strategies collectively formed a distinctive leadership typology termed Transformational Leadership with Inspirational Motivation (TLIM), which functioned as the strategic driver behind a significant rise in student achievements from 28 to 71 recorded accomplishments between 2023 and 2024 alongside strengthened institutional reputation and sustained community trust. This study contributes a contextualized TLIM model for Islamic educational management, offering empirically grounded implications for madrasah leadership development policy and practice in the Indonesian context.